JAZF1: A metabolic actor subunit of the NuA4/TIP60 chromatin modifying complex - Mameri, Amel; Côté, Jacques (Frontiers in Cell and Developmental Biology, 2023)
The multisubunit NuA4/TIP60 complex is a lysine acetyltransferase, chromatin modifying factor and gene co-activator involved in diverse biological processes. The past decade has seen a growing appreciation for its role as a metabolic effector and modulator. However, molecular insights are scarce and often contradictory, underscoring the need for further mechanistic investigation. A particularly exciting route emerged with the recent identification of a novel subunit, JAZF1, which has been extensively linked to metabolic homeostasis. This review summarizes the major findings implicating NuA4/TIP60 in metabolism, especially in light of JAZF1 as part of the complex.